Heat-shock-induced glucose transporter 4 in the slow-twitch muscle of rats - Wu, P-F; Luo, S-C; Chang, L-C (Physiological research, 2015)
In this study, lipoic acid and heat shock treatments were applied to C(2)C(12) myotubes and Sprague-Dawley rats to investigate changes in the heat shock protein 70 (HSP70) and glucose transporter 4 (GLUT4) in 4 different skeletal muscle groups. The results of western blotting indicated that treatment of lipoic acid for 24 h, heat-shock and combined lipoic acid and heat-shock which all increased the level of HSP70 substantially in C(2)C(12) myotubes. However, either lipoic acid or heat-shock did not increase the level of GLUT4 in C(2)C(12) myotubes. In an in vitro migration assay, lipoic acid increased wound migration only when it was applied for 3 h. Moreover, our in vivo results revealed that lipoic acid did not increase HSP70 and GLUT4 in all 4 different skeletal muscles. Furthermore, heat-shock increased HSP70 in all 4 different muscle groups, and heat-shock treatment alone increased the GLUT4 in the soleus muscle only, suggesting that the GLUT4 increased by heat-shock was slow-twitch muscle specific. Collectively, our results indicated that heat-shock is critical factor that modulates GLUT4 and HSP70 in the skeletal muscle of rats.
Keywords: reakce na tepelný šok; krysa rodu Rattus; zvířata; Glucose Transporter Type 4; buněčné linie; Heat-Shock Response; kosterní svaly; potkani Sprague-Dawley; Cell Line; Male; přenašeč glukosy typ 4; Muscle, Skeletal; Muscle Fibers, Slow-Twitch; svalová vlákna typu I; proteiny tepelného šoku HSP70; Rats; Rats, Sprague-Dawley; Animals; mužské pohlaví; HSP70 Heat-Shock Proteins